THE FRENCH ASPECTS IN THE EDUCATION PATTERN OF THE POLISH NOBILITY IN THE SEVENTEENTH CENTURY - Serwański, Maciej (Studia Europaea Gnesnensia, 2019)
The pattern of education of the Polish noble youth in the seventeenth century changed in comparison with the preceding century. In the latter, the mul-tinational, multicultural and multidenominational nature of the Polish-Lithuanian Commonwealth nurtured attitudes of widely understood tolerance both in terms of ideology and in practice. Poland was receptive to strong Re-naissance influence, while numerous sons of the Polish nobles studied abroad, mainly in Italy but also in Germany and France. The education system in the Jagiellonian monarchy of reflected the trends and the ideals of contemporary European education. The seventeenth century saw increased influence of the Counter-Reformation in the Nobles’ Commonwealth. The ideas of Sarmatism, embracing xenophobia, religiosity and self-glorification of the existing, petrified political system, became more pro-nounced. These tendencies were broadly present in the pattern of the educa-tion of nobility, a pattern that was prone to strong Jesuit influence in the spirit of the doctrine laid down by the Council of Trent.